Monitoring the Mental Health and Professional Overload of Health Workers in Brazil: A Longitudinal Study Considering the First Wave of the COVID-19 Pandemic - Osório, Flávia L.; Zuardi, Antonio Waldo; Silveira, Isabella L. M.; Crippa, José Alexandre S.; Hallak, Jaime Eduardo Cecílio; Pereira-Lima, Karina; Loureiro, Sonia R. (Frontiers in Psychiatry, 2022)
Few longitudinal studies assessed the less immediate consequences of the COVID-19 pandemic on health workers' mental health, especially in less developed countries. The objective was to assess the evolution of mental health indicators of Brazilian health workers providing care to COVID-19 patients, considering the beginning and first wave of the pandemic, identifying risk and protective factors. A non-probabilistic sample of health professionals was assessed for 6 months at seven different points in time using standardized instruments to measure anxiety, depression, insomnia, posttraumatic stress, and burnout symptoms. Risk and protective factors were assessed using a questionnaire addressing socio-demographic, clinical, occupational variables, and COVID-19 risk perception. The results indicate high rates for all the indicators (>30%) throughout the follow-up; only anxiety symptoms decreased in the different phases compared to the baseline. Depression and insomnia symptoms showed a significant drop in isolated points of the assessment, which were not maintained at the final follow-up. Burnout indicators concerning emotional exhaustion and depersonalization remained stable (40 and 20%), while professional achievement decreased by approximately 19%. Occupational and personal characteristics (profession and work setting), perceptions regarding protective measures imposed by the institutions, and future professional prospects stood out as risk/protective factors in mental health. Unlike European and Asian countries, where mental distress symptoms tended to decrease over the pandemic, this study's results suggest alarming indicators of mental health problems remaining stable with burnout symptoms on the rise. Hence, the different contexts across countries, with different management resources and investments in health actions, seem to influence workers' mental health differently, demanding constant attention and monitoring and measures to minimize the impacts on individuals and collectives, especially in less developed countries like Brazil.